TRANSLATION AGENCY PROJECT AS A STRATEGY IN TEACHING TRANSLATION THEORY - Farida Repelia Waty Kembaren; Muhizar Muchtar, M.S. (AICLL: ANNUAL INTERNATIONAL CONFERENCE ON LANGUAGE AND LITERATURE, 2018)
The practice of teaching translation was often done by discussing translation theories and translating texts in the classroom. However, the problem is students also need to have a real-life experience as professional translators that will be useful for them in the future. This paper presents the findings of a research study conducted in a translation class of English Education Department students in the State Islamic University of North Sumatra. The research is about Translation Agency Project as innovation strategy to teach translation subject. The students were assigned to develop their own translation agency by promoting their agency, handling the clients, and translating the texts. The objective of this research is to identify the challenges faced by the students in running their Translation Agency Project. It also includes how students cope with those challenges. Finally, it describes the benefits of using Translation Agency Project in teaching translation. The method of this research is descriptive qualitative method for translation studies (Toury, 1995) based on theoretical research compared to a survey applied to students of English Education Department who have learned about translation theories. As a result, after analyzing the data, it can be seen that the biggest challenge the students faced in conducting their translation agency is advertising the translation agency (43%), meeting with clients (36%), and translating the texts (21%). Finally, after analyzing the survey, it shows that translation Agency Project is an effective and recommended strategy to teach translation theories in the class.